Responsabilização tributária do administrador, consequencialismo e o ônus da prova: uma análise lógico-sistemática da divergência jurisprudencial entre STF e STJ. - Matos, Maria Eduarda Barbosa (2024)
The present study analyzed tax liability, limiting itself to the tax liability of administrators, which was done by adding a logical-systematic analysis of the jurisprudential divergence between the Federal Supreme Court and the Superior Court of Justice. It was necessary to investigate, through theoretical reflection and empirical study, the situation of a kind of “judicial lottery”: the unequal treatment of similar cases, which needs to be discouraged, but which today finds a shield in the divergence between the higher courts. Given this, the problem of this research is the following question: How are the foundations constructed in the judicial precedents of the STF and the STJ regarding the tax liability of administrators employed by legal entities that carry out business activities and in what legal aspects they are convergent/divergent. Furthermore, we seek to find out the legal and social consequences of these decisions. What we observed, in the end, is that there is no longer respect for patrimonial autonomy, for the limitation of responsibility, perhaps when proceeding in good faith, without fraud, without fraud, and in respect for social dictates. Practically nothing is currently researched about the abuse of legal personality as a prerequisite for holding the administrator responsible. This time, the practice and practicability of the law prevails, the presumption and the reversal of the burden of proof to the detriment of the partner and administrator, to the detriment of the entire framework of asset limitation and liability provided for and guaranteed by corporate law. All of this leading to the Active Debt Certificate absolutization of its presumption. The frustration of the legitimate expectations of partners and administrators creates an environment of extreme legal uncertainty and unpredictability, which not only affects the individual, but also the entire society in an invisible mantra of increased costs and the use of perverse subterfuges to taxation itself and economic development. Thus, analyzing the decisions of the Superior Courts, it was possible to observe a clear divergence in the established legal theses, perceiving the decisions of the STJ recurrently benefiting the tax authority, even if to do so, they have to vilify fundamental constitutional principles; and on the other, the STF, which combines a legalistic approach with a more guarantor one and thus, strives for legality, due legal process, contradiction and broad defense.